960. Implementation and Evaluation of Alcohol Screening Tool in HIV Patients. (31st December 2020) - Brickner, Evan D; Mathew, Trini; Johnson, Paul
Abstract: Background: In November 2018, the US Preventative Service Task Force (USPSTF) advised screening for Alcohol Use Disorder (AUD) in primary care settings for all adults. Given the consequences of AUD for immunocompromised patients, this recommendation was implemented using the Alcohol Use Disorders Identification Test (AUDIT) for patients with Human Immunodeficiency Virus (HIV) at Beaumont Hospital in Royal Oak, Michigan. This is a medical-student led, retrospective study to determine the impact of AUD in HIV patients that were screened using the AUDIT self-administered questionnaire. Methods: All HIV patients undergoing outpatient care at the Beaumont Hospital HIV clinic were provided this self-administered AUDIT questionnaire as part of routine, check-in procedure by clinic staff starting on February 5, 2019. Scores were divided into "At Risk" or "Not At Risk" categories. Men (aged 18-60) screened positive for at-risk drinking if they scored 8 or higher. Men (older than 60) and women of all ages screened positive for at-risk drinking if they scored 4 or higher. This categorization of risk was determined using the criteria established by the National Institute on Alcohol Abuse and Alcoholism. Analysis between groups was made using T-Tests, Chi-Square tests, and odds ratios (OR), with corresponding 95% Confidence Intervals. Results: A total of 121 HIV patients completed at least one AUDIT form. There were a total of 157 patient encounters. The mean age of "At Risk" drinkers was significantly higher than the mean age of "Not at Risk" drinkers, at initial visits and all visits, respectively (55.75 years vs. 46.25 years, p = 0.0117; 55.33 years vs. 46.29 years, p = 0.0075). These findings are depicted in Tables 1 and 2. Table 1: Differences in Health Status between "At Risk" and "Not at Risk" Individuals (Initial Visit Only) Table 2: Differences in Health Status between "At Risk" and "Not at Risk" Individuals (All Visits) Conclusion: The preliminary results of this study demonstrate the importance of screening for AUD within the vulnerable HIV patient population. More specifically, it highlights the value of screening older individuals who may be at increased risk of hazardous drinking. In March 2020, the COVID-19 pandemic required transitioning to a telemedicine platform, thereby preventing completion of AUDIT paper forms. Thus, we will leverage technology by incorporating the AUDIT into electronic medical records, in effort to fortify this quality improvement initiative and ensure patient centered care. Disclosures: All Authors : No reported disclosures